2018
DOI: 10.3389/fmars.2018.00090
|View full text |Cite
|
Sign up to set email alerts
|

TurtleCam: A “Smart” Autonomous Underwater Vehicle for Investigating Behaviors and Habitats of Sea Turtles

Abstract: Sea turtles inhabiting coastal environments routinely encounter anthropogenic hazards, including fisheries, vessel traffic, pollution, dredging, and drilling. To support mitigation of potential threats, it is important to understand fine-scale sea turtle behaviors in a variety of habitats. Recent advancements in autonomous underwater vehicles (AUVs) now make it possible to directly observe and study the subsurface behaviors and habitats of marine megafauna, including sea turtles. Here, we describe a "smart" AU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Traditional methods include direct observation using snorkel or SCUBA (Reisser et al 2013), the analysis of gut contents from dead turtles (Mortimer 1981) and oesophageal lavage and faecal examination (Seminoff et al 2002), while indirect biochemical approaches include stable isotope analysis (SIA) (Pearson et al 2017). Modern technologies, such as remote videography (Letessier et al 2014), animal-borne cameras (Heithaus et al 2002), autonomous underwater vehicles (Dodge et al 2018) as well as satellite tracking from nesting beach and subsequent in situ validation of diet at foraging locations (Esteban et al 2018), have also been used to document the activities of turtles at their foraging habitats.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Traditional methods include direct observation using snorkel or SCUBA (Reisser et al 2013), the analysis of gut contents from dead turtles (Mortimer 1981) and oesophageal lavage and faecal examination (Seminoff et al 2002), while indirect biochemical approaches include stable isotope analysis (SIA) (Pearson et al 2017). Modern technologies, such as remote videography (Letessier et al 2014), animal-borne cameras (Heithaus et al 2002), autonomous underwater vehicles (Dodge et al 2018) as well as satellite tracking from nesting beach and subsequent in situ validation of diet at foraging locations (Esteban et al 2018), have also been used to document the activities of turtles at their foraging habitats.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…However, this approach augments considerably the tag's size and, therefore, is not suitable for smaller tags. The tag's size is also an important constraint in (20). In (14), the authors developed a method that used the signal strength to infer the tag's position; nonetheless, its performance and observability studies were not reported.…”
Section: Aott Algorithmmentioning
confidence: 99%
“…These technologies can help expand research activities over longer time periods or larger areas, including shallow coastal regions inaccessible by large research vessels (Cokelet et al 2015, Rudnick 2016. Recently, autonomous underwater vehicles (AUVs) have been used for focal follow type studies of fish, sharks, and turtles (Packard et al 2013, Skomal et al 2015, Dodge et al 2018). These studies, which used acoustic transponders on the targeted animal, were temporally limited (1 to < 8 h) and only able to measure oceanographic parameters, not prey abundance (Packard et al 2013, Skomal et al 2015, Dodge et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, autonomous underwater vehicles (AUVs) have been used for focal follow type studies of fish, sharks, and turtles (Packard et al 2013, Skomal et al 2015, Dodge et al 2018). These studies, which used acoustic transponders on the targeted animal, were temporally limited (1 to < 8 h) and only able to measure oceanographic parameters, not prey abundance (Packard et al 2013, Skomal et al 2015, Dodge et al 2018. For focal follow studies with unmanned vehicles to be comparable to traditional survey methods, longer follow durations and direct measurements of prey are needed.…”
Section: Introductionmentioning
confidence: 99%